Single‐Particle Measurement: A Valuable Method for Studying Structural Evolution of Battery and Performance Degradation - Xin Zhang; Na Li; Xu Li; Le Yang; Wei‐Li Song; Ya‐Na Wang (ChemElectroChem)
Abstract Active particle materials with high capacity, safety, and abundance, such as Sn and Si‐based materials, and nickel‐rich layered materials like LiNixCoyMn1−x−yO2 (with x≥0.8) are viewed as promising candidates for the evolution of next‐generation batteries. However, structural degradation during cycling often limits the application of these active particle materials. Currently, research efforts are focused on developing new characterization techniques to understand the structural degradation mechanisms of active particle materials during the cycle, to improve their performance. This paper reviews advanced single‐particle electrochemical and structural characterization techniques and their main findings. These findings included lattice displacement and rotation, microstructure evolution, and reaction kinetics of single‐particle during cycling. In addition, we also discuss the potential future applications and developments of single‐particle measurement technologies.